SELF-EDUCATION IN THE PROFESSIONAL SYSTEM PREPARATION OF FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2022)
The article of Dudnik N. is dedicated to the problem of selfeducation, different ways to definition of this process, its role in the professional prepearing of a future teacher.